Implementasi Sistem Point of Sale (POS) pada UMKM Kuliner dengan Pendekatan COSO dan TAM - Kurnia Indri Yani; Bambang Widarno (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This research aims to analyze the implementation of the Point of Sale (POS) system in culinary MSMEs in Solo Raya using the Committee of Sponsoring Organizations of the Treadway Commission (COSO) and Technology Acceptance Model (TAM) approaches. Through a qualitative descriptive method with interview, questionnaire, and documentation techniques, the results indicate that the effectiveness of COSO-based internal control has been performing well, as evidenced by the audit trail feature to mitigate the risk of data manipulation, while from the TAM perspective, users show a very high level of technology acceptance as the system provides ease, benefits, and a positive usage attitude in accelerating financial reporting. However, constraints were found in the accountability aspect due to the practice of using shared accounts among staff, making personal transaction tracking difficult to perform. Thus, although efficiency and digital control are already strong, strengthening authorization procedures and user identity is necessary to enhance overall system integrity